Rare Copy Number Variants in Array-Based Comparative Genomic Hybridization in Early-Onset Skeletal Fragility - Costantini, Alice; Skarp, Sini; Kämpe, Anders; Mäkitie, Riikka E.; Pettersson, Maria; Männikkö, Minna; Jiao, Hong; Taylan, Fulya; Lindstrand, Anna; Mäkitie, Outi (Frontiers in Endocrinology, 2018)
Early-onset osteoporosis is characterized by low bone mineral density (BMD) and fractures since childhood or young adulthood. Several monogenic forms have been identified but the contributing genes remain inadequately characterized. In search for novel variants and novel candidate loci, we screened a cohort of 70 young subjects with mild to severe skeletal fragility for rare copy-number variants (CNVs). Our study cohort included 15 subjects with primary osteoporosis before age 30 years and 55 subjects with a pathological fracture history and low or normal BMD before age 16 years. A custom-made high-resolution comparative genomic hybridization array with enriched probe density in > 1150 genes important for bone metabolism and ciliary function was used to search for CNVs. We identified altogether 14 rare CNVs. Seven intronic aberrations were classified as likely benign. Five CNVs of unknown clinical significance affected coding regions of genes not previously associated with skeletal fragility (ETV1-DGKB, AGBL2, ATM, RPS6KL1-PGF and SCN4A). Finally, two CNVs were pathogenic and likely pathogenic, respectively: a 4 kb deletion involving exons 1-4 of COL1A2 (NM_000089.3) and a 12.5 kb duplication of exon 3 in PLS3 (NM_005032.6). Although both genes have been linked to monogenic forms of osteoporosis, COL1A2 deletions are rare and PLS3 duplications have not been described previously. Both CNVs were identified in subjects with significant osteoporosis and segregated with osteoporosis within the families. Our study expands the number of pathogenic CNVs in monogenic skeletal fragility and shows the validity of targeted CNV screening to potentially pinpoint novel candidate loci in early-onset osteoporosis. Key words: osteoporosis; bone fracture; cilia; copy number variant (CNV); array CGH